Upaya Meningkatkan Motivasi Belajar Bahasa Inggris Melalui Media Brosur Bimbingan Belajar dan Diskusi Kelompok pada Siswa SMP - Sarleni Rhepon (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
This study aims to increase the motivation to learn English through brochures tutoring and group discussions to junior high school students in orphanages orphaned daughter 'Aisyiyah. This research is action research (action research) with reference to the research design and Mc Taggart Kemmis. Subjects numbered nineteen people. Data collection instrument using a Likert scale of learning motivation, observation guidelines, and guidelines for the interview. Data analysis using t-test results showed that posttest Nineteen students are in good category, with a score percentage is between 76% - 100%. Based on the results of this study concluded that the media brochure tutoring and group discussions can increase motivation to learn English junior high school students in orphanages orphaned daughter `Aisyiyah. The results of this study can be used by counselors in helping students improve motivation to learn English through brochures tutoring and group discussions.